Orderly principles of state administration in selecting ministers - Ariyanto, Bambang; Maulana Kafrawi, Rachman (Legality : Jurnal Ilmiah Hukum, 2022)
One of the advantages of the presidential system is the president's authority to appoint ministers without the intervention of others. The President's authority has been confirmed in Article 17 paragraph (4) of the Constitution 1945 which states that the President appoints and dismisses ministers. This regulation is also emphasized by the existence of Law Number 39 of 2008 concerning the Ministry of the State which states that ministers are assistants to the president in leading Ministry. The State Ministry Law does not set limits on how persons can be elected by the president to become ministers, whether from political parties, professionals, academics, practitioners; it is all purely the authority of the president. Limitations on ministerial candidates are only regulated in the Constitutional Court Decision Number 79/PUU-IX/2011asserting that the positions of ministers and ministries may not be sold as a political gift to a person or a group. On that basis, the question regarding what legal principles in the state administrative law can be referred to by the president in forming a competent cabinet is raised. With normative-juridical methods, the purpose of this paper is to find out the principles in state administrative law in the implementation of government, especially in cabinet elections. The results of the study show that the principle of the orderly administration of the state must serve as a reference in the implementation of government, especially in cabinet elections. This principle involves the basis of order, harmony, and balance in state control and administration. Besides, the ministers appointed by the president must avoid and be aware of the occurrence of maladministration that leads to liability personal, not job responsibilities. To strengthen the principle of orderly state administration, The Ministry of State must include this principle in one of its articles.